Seismic retrofitting of structural elements. An experimental characterization - Pedro Delgado (2005)
Many structures representative of the typical construction of the seventies were designed based on codes without adequately considering the seismic design, thus probably lacking structural safety when compared with structures designed according to new codes. Such structures are very likely to require retrofit interventions that should be thoroughly assessed both in terms of the technical feasibility and economical viability, bearing in mind the huge number of existing structures in such conditions. In that context, this paper presents different seismic retrofit techniques applied to reinforced concrete elements numerically simulated and experimentally tested under cyclic loads. The paper first addresses the experimental setup, specially designed to perform biaxial bending with axial load using two horizontal and orthogonal actuators and one vertical actuator (the later with a slide device to allow top displacements of the column) and proceeds with the presentation of the test campaign on several RC columns presently underway at the Laboratory of Earthquake and Structural Engineering of the Faculty of Engineering of the University of Porto. Some comparisons between the experimental results and numerical simulation for cyclic response prediction are also presented and, as a key-issue of the work, the structural safety improvement achieved with each of the adopted retrofit techniques is also discussed. In line with this, the basic aim is therefore to contribute for development and calibration of a procedure that enables the efficiency evaluation for different retrofit solutions and clearly establishes their possibilities and fields of application.